A Narrative Analysis Using the Concept of Tabligh on the Obligation of Financial Statements Disclosure - Aziza , Nur; A. Birton , M. Nur (KnE Social Sciences, 2019)
Facts show that the rate of the disclosure ﬁnancial statements by full-ﬂedged sharia ﬁnancecompaniesinIndonesiaisstillhighlylimited.Outofthreecompanies,onlyPT.Al Ijarah Indonesia Finance which give full and voluntary ﬁnancial statements disclosure. This research aims to reveal the motivation of ﬁnancial statements disclosure by full-ﬂedged sharia ﬁnance companies using the concept of tabligh. This research uses theparadigmof tauhidandqualitativeapproach.Dataiscollectedbyintervieweingfour key informants from PT Al Ijarah Indonesia Finance to uncover motives and document study. Data is analyzed using Greimas’ structural narrative analysis and combined with the concept of tabligh. The results of the research show that the motive of ﬁnancial statements disclosure by PT Al Ijarah Indonesia Finance is to communicate (tabligh) the ﬁnancial statements to the stakeholders so that a broad and clear picture of the company is provided. Communicating (tabligh) informations broadly and clearly is what PT Al Ijarah Indonesia Finance aims for, which can be explained in several narrative relations; ﬁrst, internal relations in which the constraints of ALIF internal disclosure become the consideration for the publication goodwill, which when combined with the concept of tabligh becomes the foundation of the disclosure. Second, the extent and content of the disclosure in the relation of subject and object as an informative disclosure, and when combined with the concept of tabligh becomes an extensive disclosure. The last relation is the disclosure media as the target of disclosure in the relation of sender and receiver, so that when combined with the concept of tabligh it becomes an effective act of communication.